Increment of Antimycobaterial Activity on Lichexanthone Derivatives - Micheletti, Ana Camila; Honda, Neli Kika; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Cepa Matos, Maria de Fatima; Perdomo, Renata Trentin; Bogo, Danielle; Alcantara, Glaucia Braz; Beatriz, Adilson (Bentham Science Publ Ltd, 2013)
A new dihydropyranexanthone derived from the natural xanthone lichexanthone (1) was synthesised and, together with other 18 derivatives including omega-bromo and omega-aminoalkoxylxanthones (containing methyl, ethyl, propyl, tert-butylamino and piperidinyl moieties), were tested against Mycobacterium tuberculosis. Nine omega-aminoalkoxylxanthones showed good antimycobacterial activity, and their in vitro cytotoxicity was determined using VERO cells in order to calculate the selectivity index (SI). One of these nitrogenated xanthone derivatives showed very promising results, with MIC of 2.6 mu M and SI of 48. This MIC is comparable to values found in first and second line drugs commonly used to treat TB. In order to understand better about this compound, it was evaluated together with two other ones that showed good SI, against resistant clinical strains of M. tuberculosis to verify the existence of cross-resistance. A chemometrical approach was useful to establish a pattern of antitubercular activity among the group of -aminoalkoxylxanthones, according to some structural and chemical features.
Keywords: Chemometrics; lichen; structural modifications; tuberculosis; xanthone